Serotonin and amyloid deposition: a link between depression and Alzheimer’s disease? : Editorial highlight - Gründer, Gerhard; Cumming, Paul (Journal of neurochemistry, 2021)
Indirect agonism has been invoked as part of the mechanism of antipsychotic action at dopamine D2/3 receptors, and more recently as a salient neuropharmacological aspect of the serotonin 5-HT2A drug pimavanserin (Pim). We now comment on an article in this volume showing that Pim treatment attenuates the deposition of Aβ protein in brain of transgenic Alzheimer's disease model mice. Pim treatment may interfere with Aβ deposition by shifting the balance between two 5-HT2A signaling pathways, that is, antagonism of Gq/11 signaling and agonism of Gαi1 signaling. Treatment with serotonin-selective reuptake inhibitors (SSRIs) evoked also reduced amyloid deposition in transgenic mice, but SSRI treatment does not unequivocally interfere in the progression of human Alzheimer's disease, perhaps because of complex effects of chronic SSRI treatment on multiple serotonin receptor types. Preclinical findings suggest Pim as a promising pharmacological strategy for intervening against Alzheimer's pathology, perhaps at a very early stage of the disease. However, much remains to be learned about the convergence of various receptor-mediated signaling pathways on the final common path leading to net Aβ deposition.
Gesehen am 18.08.2021